DEVELOPMENT AND IMPLEMENTATION OF A FIVE-TIER DIAGNOSTIC TEST TO IDENTIFY STUDENT MISCONCEPTIONS ON FRACTIONS: A SIGNIFICANT STEP TOWARDS IMPROVING MATHEMATICS EDUCATION - Herliana, Herliana; Maison, Maison; Syaiful, Syaiful (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
Misconceptions in fractions, a significant challenge in mathematics education, occur when students' conceptions do not align with scientific conceptions, yet they firmly believe in the correctness of their conceptions. These deeply rooted misconceptions are difficult to eliminate and not easily identified with conventional instruments. Therefore, this study aims to develop a valid and reliable five-tier diagnostic test instrument to identify students' misconceptions about fractions effectively. The design of this development research involves qualitative and quantitative methods using the 4D model (define, design, develop, disseminate). Sixty-eight seventh-grade students were involved in quantitative instrument quality testing; data were analyzed using SPSS. The final result of the development of this instrument was 12 questions declared valid and reliable. Furthermore, the instrument was applied to 30 seventh-grade students in different schools to identify their misconceptions about fractions. Based on the analysis of the combination of students' answers, it was obtained that 36.4% of students understood the concept, 8.9% were in the false positive category, 7.2% were false negative, 9.7% lacked knowledge, and 37.8% had misconceptions. It was found that the most dominant description of misconceptions (33%), namely, students assume that the smaller the denominator of a fraction, the smaller the value of the fraction. Then, it was also found that students' thinking, in general, causes misconceptions to occur. The practical implication of the results of this study is that teachers can use the instrument and identify misconceptions to develop more effective teaching methods, thereby improving mathematics education by helping students avoid and anticipate misconceptions.